Assessing the real-world effectiveness of five SARS-CoV-2 vaccines in a cohort of Mexican pensioners: a nationwide nested test-negative design studyResearch in context - Mauricio Hernandez-Avila; Edgar Ortiz-Brizuela; Marcela Tamayo-Ortiz; Rodrigo Zepeda-Tello; Héctor Gutierrez-Diaz; David Barros-Sierra Cordera; Waldo Vieyra-Romero; Gabriel Alejandro Real-Ornelas; Mauricio Méndez Aranda; Antonio Heras Gómez (Elsevier, 2023)
Summary: Background: Despite the extensive distribution of COVID-19 vaccines across Latin America, research on their real-world performance remains limited. We aimed to evaluate the effectiveness of five vaccines (BNT162b2, AZD1222, CoronaVac, Gam-COVID-Vac, and Ad5-nCoV) in a cohort of 2,559,792 pensioners covered by the Mexican Institute of Social Security. Methods: We conducted a nested test-negative design study on 28,271 individuals tested for SARS-CoV-2 infection between April and November 2021, accounting for 29,226 separate episodes. We used mixed-effects logistic regression models to estimate the vaccine effectiveness (VE) in fully vaccinated individuals for symptomatic infection, hospitalization, severe disease, and death. Findings: The median age of the study population was 70 years (interquartile range 65-76) and 76.4% (21,598/28,271) were male. VE rates were 56.3%, 75.3%, 79.7%, and 79.8% against symptomatic infection (95% confidence interval [CI]: 53.5-59.0), hospitalization (95% CI: 73.4-77.0), severe disease (95% CI: 78.0-81.3), and death (95% CI: 78.1-81.4), respectively. When evaluating vaccines individually, all showed moderate to high VE, with the best being BNT162b2 (symptomatic infection, 69.8%, 95% CI: 67.3-72.0; hospitalization, 84.1%, 95% CI: 82.5-85.6; severe disease, 88.2%, 95% CI: 86.7-89.5; and death, 88.3%, 95% CI: 86.9-89.6) and Gam-COVID-Vac (symptomatic infection, 70.0%, 95% CI: 64.8-74.4; hospitalization, 86.8%, 95% CI: 83.7-89.3; severe disease, 91.9%, 95% CI: 89.4-93.9; and death, 92.0%, 95% CI: 89.5-93.9). Interpretation: All five SARS-CoV-2 vaccines available for this population showed moderate to high levels of protection against COVID-19 and its progression to severe outcomes. Funding: Fundación IMSS, México.